Interaction between Common and Siberian Chiffchaff in a contact zone - Marova, Irina; Shipilina, Daria; Fedorovk, Vjatcheslav; Alekseev, Valery; Ivanitskii, Vladimir (BirdLife Finland, 2017)
The study of hybridization between closely related taxa of animals sheds light on many important issues of evolution biology and taxonomy. Common Chiffchaff (Phylloscopus collybita abietinus) and Siberian Chiffchaff (Ph. c. tristis) co-occur in an extended zone of sympatry in the area from theWhite Sea to the South Urals. In allopatric populations, these two races are well differentiated in the external appearance and song. Under sympatric conditions, individuals with intermediate appearance and vocalizations are found practically everywhere but the occurrence of hybridization has not been documented up to date. The article describes the results of our study of interrelations between Common and Siberian Chiffchaffs in mixed populations found in the Arkhangelsk Region, the Komi Republic, and the Southern UralMountains. Allopatric populations were studied in central Russia (Moscow and Kostroma regions) and central Siberia (Yenisey River and SayanMountains). Inmixed populations, 30.2% of the individuals with species specific phenotype showed a phenotype/haplotype mismatch while there were no such mismatches in allopatric populations. 58.7% of the individuals with typical abietinus phenotypes carried tristis haplotypes while only 4.0% possessed the opposite phenotype/ haplotype combination. Most of the individuals with intermediate phenotype had tristis haplotypes (97.6%). Only 9.8% of the individuals with known haplotypes performed mismatched songs. Inmixed populations, 9 of 11males clearly responded to the playback of the song of another taxa while in allopatry no such reactions were observed for the 14 males tested. Our results strongly suggest hybridization between abietinus and tristis in the mixed populations.